2005
DOI: 10.1042/bst20051210
|View full text |Cite
|
Sign up to set email alerts
|

Azole susceptibility and resistance in Candida dubliniensis

Abstract: Candida dubliniensis is a recently described species of pathogenic yeast that shares many phenotypic features with Candida albicans. It is primarily associated with oral colonization and infection in HIV-infected individuals. Isolates of C. dubliniensis are generally susceptible to commonly used azole antifungal agents; however, resistance has been observed in clinical isolates and can be induced by in vitro exposure. Molecular mechanisms of azole resistance in C. dubliniensis include increased drug efflux, mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Few authors have suggested that Candida dubliniensis is capable to produce germ tube as well as chlamydospores, its ability shared only with the closely related species C. albicans but the difference is that this species is unable to grow at 42-45°C[22] and is recovered primarily from the oral cavities of human immunodeficiency virus (HIV)-infected individuals and AIDS patients . [2324]…”
Section: Discussionmentioning
confidence: 99%
“…Few authors have suggested that Candida dubliniensis is capable to produce germ tube as well as chlamydospores, its ability shared only with the closely related species C. albicans but the difference is that this species is unable to grow at 42-45°C[22] and is recovered primarily from the oral cavities of human immunodeficiency virus (HIV)-infected individuals and AIDS patients . [2324]…”
Section: Discussionmentioning
confidence: 99%
“…However, azole resistance was not affected by efflux pump inhibitors, suggesting that efflux-mediated resistance is not due to efflux pumps alone in C. krusei [69]. Increased efflux pump expression also correlates with increased azole resistance in C. parapsilosis and C. dubliniensis [70,71].…”
Section: Over-expression Of Membrane Transportersmentioning
confidence: 96%
“…Since germ tube test is routinely used for the differentiation of C. albicans from other Candida species, identification based solely on this test leads to misidentification of some C. albicans isolates in routine diagnostic laboratories [5]. Accurate identification is warranted since C. dubliniensis exhibits increased adherence to buccal epithelial cells and is more likely to develop resistance against fluconazole and other azoles [6,7]. …”
Section: Introductionmentioning
confidence: 99%